The impact of digital transformation on the overall performance of The Ministry of Finance – Gaza - Abu Lehea, Israa Jomaa Ahmed (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to know the impact of digital transformation on the overall performance of the Ministry of Finance - Gaza, The researcher was able, through the method of the quantitative - deductive method, to define the phenomenon of research in general down to the molecules, and then collect data and analyze them with the study tool (questionnaire), and the study population is represented by (beneficiaries of services provided by the Ministry of Finance), as well as the study sample consisted of 50 Individuals who benefited from these services during a period of time between January and May 2023. The study reached the following results: 1- Digital transformation is considered one of the priorities of the Ministry of Finance to develop its overall performance, and within its strategic plan for the year 2022-2023. 2- There is no specific definition of the concept of digital transformation due to its connection to the sustainable technological revolution. 3- The importance of digital transformation in institutions, especially governmental institutions, is that it achieves many positive aspects related to entrepreneurship, innovation, and performance development.